Preparation method of oxygen solute gradient amorphous high-entropy alloy oxidation coating
By depositing a high-entropy alloy coating on the substrate surface and performing thermal oxidation treatment, an oxygen-solute gradient amorphous AlCrYTiZrO coating is formed, which solves the problem of insufficient performance of existing corrosion-resistant coatings and achieves higher corrosion resistance and adhesion.
Patent Information
- Application Number
- CN202511670112.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-01-27
AI Technical Summary
Existing corrosion-resistant coatings have poor corrosion resistance and cannot effectively protect the mechanical motion system components of marine equipment from corrosion damage during long-term service in the marine environment.
A high-entropy alloy coating was deposited on the substrate surface by magnetron sputtering and then thermally oxidized in an air atmosphere to form an amorphous AlCrYTiZrO high-entropy oxide coating with an oxygen solute gradient. The corrosion resistance of the coating was enhanced by element diffusion and the oxygen solute gradient structure.
It improves the corrosion resistance of the coating, enhances the adhesion between the coating and the substrate, forms a dense oxygen solute gradient structure, significantly reduces the self-corrosion current density, and improves the hardness and stability of the coating.
Smart Images

Figure CN121407035A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of material surface treatment technology, specifically to a method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating. Background Technology
[0002] Marine resources are abundant and possess significant economic value and strategic importance for national defense. With the development of the maritime power strategy, higher demands are being placed on the reliability and service life of marine equipment. The mechanical motion systems of marine equipment operate in the marine environment for extended periods, and the surfaces of these components are subject to chemical / electrochemical corrosion, accelerating damage and failure.
[0003] Currently, existing technologies achieve protective effects by preparing corrosion-resistant coatings on the surface of in-service components. However, the corrosion resistance of existing corrosion-resistant coatings is relatively poor. Summary of the Invention
[0004] Therefore, the purpose of this invention is to provide a method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating to improve corrosion resistance.
[0005] A method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating includes the following steps: Step S11: The substrate after ultrasonic cleaning and drying is sent into the cavity, and a high-entropy alloy coating is deposited on the surface of the substrate by magnetron sputtering. Then, it is cooled to room temperature. The high-entropy alloy target is an AlCrYTiZr alloy target with an equiatomic ratio. Step S12: The substrate containing the high-entropy alloy coating is placed in an oxidation furnace, thermally oxidized in an air atmosphere, and then cooled to room temperature with the furnace to obtain the AlCrYTiZrO high-entropy oxide coating.
[0006] Preferably, the AlCrYTiZrO high-entropy oxide coating has an amorphous structure containing an oxygen solute gradient, and the oxygen solute gradually decreases from the coating surface toward the substrate. AlCrYTiZr alloying elements and matrix elements diffuse into each other at the interface between the coating and the matrix, forming a diffusion layer.
[0007] Preferably, the AlCrYTiZrO high-entropy oxide coating has a thickness of 1~2 μm, and the diffusion layer has a thickness of 50~70 nm.
[0008] Preferably, the AlCrYTiZrO high-entropy oxide coating has a hardness of 15.29~18.28 GPa and a self-corrosion current density of 2.36×10⁻⁶. -8 ~2.7×10 -9 A / cm 2 .
[0009] Preferably, in step S11, the magnetron sputtering uses a DC power supply of 100-200W, a deposition gas pressure of 0.2-0.3Pa, a deposition time of 30min, and a deposition temperature of room temperature.
[0010] Preferably, in step S12, the temperature of thermal oxidation is below 450°C, the heating rate is 15~20°C / min, and the holding time is 0~60min.
[0011] Preferably, in step S11, the substrate is subjected to plasma bombardment cleaning before magnetron sputtering, and then the high-entropy alloy target is pre-sputtered.
[0012] Preferably, the atomic ratio of each element in the high-entropy alloy target is 20%.
[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: First, the AlCrYTiZrO high-entropy oxide coating has a large number of components, a large mixing entropy, a low Gibbs free energy, and a relatively stable system. Among them, aluminum has a low density, which significantly reduces the overall density of the alloy; chromium has excellent corrosion resistance; yttrium can refine grains and strengthen the second phase; titanium has high specific strength and corrosion resistance; zirconium has corrosion resistance and solid solution and precipitation strengthening characteristics. Through the complementary characteristics of single elements, the synergistic effect of multiple elements, and the unique "cocktail effect" of high entropy, excellent corrosion resistance is generated. Secondly, thermal oxidation in an air atmosphere can introduce small-radius oxygen atoms into the coating, exacerbating the degree of atomic size mismatch (atomic disorder) and forming an amorphous structure with an oxygen solute gradient, which further improves corrosion resistance. At the same time, AlCrYTiZr alloying elements and matrix elements diffuse into each other at the interface between the coating and the matrix, forming a diffusion layer that can enhance the bonding force between the coating and the matrix. Attached Figure Description
[0014] Figure 1 This is a schematic diagram of the preparation method of the oxygen-solute gradient amorphous high-entropy alloy oxide coating proposed in this invention; Figure 2 The enthalpy of mixing of different atom pairs in the coating prepared by this invention; Figure 3 Grazing incidence of high-entropy alloy films with different oxygen contents in this invention; Figure 4 (a~d) are SEM images of the surface morphology of AlCrYTiZrO coatings with different O contents; Figure 4 (e~h) is Figure 4 Enlarged view of the selected areas in (a~d); Figure 4(i~l) are SEM images of the cross-sectional morphology of AlCrYTiZrO coatings with different O contents; Figure 4 (m~p) represents the line scan data of the thin film cross-section; Figure 5 (a) is a schematic diagram of the O-3 coating / X70 steel substrate (6×2.4μm) sample prepared by FIB in this invention; Figure 5 (b) is a TEM image of the cross-section of the O-3 coating (confirming...). Figure 4 (Analysis of (k)); Figure 5 (c) is an HRTEM image of the cross-section of the O-3 coating; Figure 5 (d) is the energy dispersive spectroscopy (EDS) diagram corresponding to the O-3 coating; Figure 5 (e) is a line scan of the cross-sectional interface of the O-3 coating; Figure 5 (f) shows the HRTEM image of the cross-section of the O-3 coating interface and the corresponding EDS element distribution map; Figure 6 (a) Load-displacement curves of nanoindentation of AlCrYTiZrO coatings with different oxygen contents in this invention; Figure 6 (b) Load-displacement curves of the hardness of AlCrYTiZrO coatings with different oxygen contents in this invention; Figure 6 (c) Load-displacement curves of the elastic modulus of AlCrYTiZrO coatings with different oxygen contents in this invention; Figure 7 (a) Tafel plots of HEA with different oxygen contents in 3.5 wt% sodium chloride solution under OCP conditions; Figure 7 (b) Nyquist plots of HEA with different oxygen contents in 3.5 wt% sodium chloride solution under OCP conditions; Figure 7 (c) Bode plots of HEA with different oxygen contents in 3.5 wt% sodium chloride solution under OCP conditions; Figure 7 (d) is the equivalent electronic circuit (EEC) model that fits the EIS experimental data.
[0015] The following detailed description, in conjunction with the accompanying drawings, will further illustrate the present invention. Detailed Implementation
[0016] The following description is intended to disclose the invention and enable those skilled in the art to implement it. The preferred embodiments described below are merely examples, and other obvious variations will occur to those skilled in the art.
[0017] It should be noted that this invention employs a magnetron sputtering co-sputtering method to deposit an AlCrYTiZr high-entropy alloy on the surface of an ultrasonically cleaned steel substrate. The principle behind this is the generation of Ar gas through Ar ionization. + Ions, accelerated by the cathode potential, bombard the cathode target (AlCrYTiZr), sputtering target atoms and secondary electrons. The target atoms deposit onto the anode substrate in the opposite direction. The secondary electrons, moving perpendicular to the electric and magnetic fields in the orthogonal electromagnetic field, exhibit a rolling trajectory, enhancing collisions with Ar molecules and increasing the probability of Ar ionization. The key advantages of this technology are high ionization rate, fast deposition rate, low operating temperature, and controllable element content, minimizing target element agglomeration and backsputtering phenomena that could lead to microstructure inhomogeneity. Natural cooling to room temperature in the vacuum coating chamber avoids rapid oxidation upon exposure to air. Finally, thermal oxidation is performed in a muffle furnace, introducing small-radius atomic oxygen to form an oxygen-solubilized amorphous AlCrYTiZr high-entropy oxide coating.
[0018] Please see Figure 1 An embodiment of the present invention provides a method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating, comprising: Step 1: Polish and clean the steel substrate.
[0019] Polish the substrate to a mirror finish using polishing compound, then ultrasonically clean it sequentially in chemically pure acetone and ethanol for 10 minutes each. Finally, quickly dry it with a hair dryer until the surface is clean and free of stains. Polishing and ultrasonic cleaning of the substrate helps improve the bonding strength between the high-entropy alloy and the substrate.
[0020] It should be noted that in this application, the steel substrate can be made of stainless steel or pipeline steel.
[0021] Step 2: Under vacuum conditions, an AlCrYTiZr alloy target is deposited on the substrate by magnetron sputtering to prepare an AlCrYTiZr alloy coating. The specific method is as follows; The ultrasonically cleaned substrate was fixed onto the substrate platform of the magnetron sputtering coating chamber, and a vacuum was evacuated to a back-bottom vacuum level of 1×10⁻⁶. -3 Below Pa, an AlCrYTiZr alloy coating was then deposited by sputtering using an AlCrYTiZr alloy target. It should be noted that before magnetron sputtering, the substrate was subjected to plasma bombardment cleaning to remove surface impurities and enhance substrate activity. Then, the high-entropy alloy target was pre-sputtered to remove oxides from the target surface.
[0022] The AlCrYTiZr alloy target has an atomic ratio of Al:20%, Cr:20%, Y:20%, Ti:20%, and Zr:20%. The DC power supply is 100-200W, the deposition gas pressure is 0.2~0.3Pa, the deposition time is 30min, and the deposition temperature is room temperature.
[0023] Step 3: Cool the AlCrYTiZr high-entropy alloy coating prepared in Step 2 to room temperature in the furnace.
[0024] Because sputtered atoms bombard the substrate for a long time during the deposition process, the resulting AlCrYTiZr high-entropy alloy coating will have a certain temperature rise. After the deposition is completed, the sample is cooled fully in the high vacuum coating chamber before being removed to ensure that the sample surface is not oxidized by air.
[0025] Step 4: Place the substrate containing the high-entropy alloy coating into an oxidation furnace, perform thermal oxidation in an air atmosphere, and then cool it to room temperature with the furnace to obtain the AlCrYTiZrO high-entropy oxide coating. The thermal oxidation temperature is below 450℃, the heating rate is 15~20℃ / min, and the holding time is 0~60min.
[0026] It should be noted that, firstly, the AlCrYTiZrO high-entropy oxide coating has a large number of components, a large mixing entropy, a low Gibbs free energy, and a relatively stable system. Among them, aluminum has a low density, which significantly reduces the overall density of the alloy; chromium has excellent corrosion resistance; yttrium can refine grains and strengthen the second phase; titanium has high specific strength and corrosion resistance; and zirconium has corrosion resistance and solid solution and precipitation strengthening characteristics. Through the complementary characteristics of single elements, the synergistic effect of multiple elements, and the unique "cocktail effect" of high entropy, excellent corrosion resistance is generated. Second, in this application, thermal oxidation in an air atmosphere can introduce small-radius oxygen atoms into the coating, exacerbating the degree of atomic size mismatch (atomic disorder), making the AlCrYTiZrO high-entropy oxidation coating an amorphous structure containing an oxygen solute gradient, and the oxygen solute gradually decreases from the coating surface toward the substrate, thereby further improving the corrosion resistance of the coating. After thermal oxidation, the aluminum-chromium-yttrium-titanium-zirconium high-entropy oxide coating needs to be cooled to room temperature with the furnace, so that the AlCrYTiZr alloying elements and matrix elements diffuse into each other at the interface between the coating and the matrix, forming a diffusion layer, which can enhance the bonding force between the coating and the matrix.
[0027] Preferably, the AlCrYTiZrO high-entropy oxide coating has a thickness of 1~2 μm, and the diffusion layer has a thickness of 50~70 nm. The hardness of the AlCrYTiZrO high-entropy oxide coating is 15.29~18.28 GPa, and the self-corrosion current density is 2.36 × 10⁻⁶. -8 ~2.7×10 -9 A / cm2 .
[0028] The preparation method of this application will be described in detail below with different embodiments: Example 1 (Sample O-1) Step 1: Polish the substrate to a mirror finish with polishing compound, then ultrasonically clean it in chemically pure acetone and ethanol for 10 minutes in sequence, and then quickly dry it with a hair dryer.
[0029] Step 2: Fix the substrate onto the base stage of the magnetron sputtering coating chamber, and evacuate to a background vacuum level of 1×10⁻⁶. -3 Below Pa.
[0030] Step 3: An AlCrYTiZr alloy coating is deposited on the steel substrate by DC magnetron sputtering. The AlCrYTiZr alloy target has an atomic ratio of Al:20%, Cr:20%, Y:20%, Ti:20%, and Zr:20%. The DC power supply is 100-200W, the deposition gas pressure is 0.2Pa, the deposition temperature is room temperature, the substrate rotation speed is 1r / min, the target is directly facing the target and sputtered, and the deposition time is 30min.
[0031] Step 4: The prepared AlCrYTiZr high-entropy alloy coating is cooled to room temperature in the furnace, and the thickness of the resulting AlCrYTiZr high-entropy alloy is 1 μm.
[0032] The microstructure and mechanical properties of the prepared AlCrYTiZr high-entropy alloy were characterized. The alloy structure was amorphous, and the elements Al, Cr, Y, Ti, and Zr were uniformly distributed. The hardness was measured to be 11.09 GPa under a 10 mN load by nanoindentation. Electrochemical testing showed a self-corrosion current density of 3.93 × 10⁻⁶. -8 A / cm 2 .
[0033] Example 2 (Sample O-2) Step 1: Polish the substrate to a mirror finish with polishing compound, then ultrasonically clean it in chemically pure acetone and ethanol for 10 minutes in sequence, and then quickly dry it with a hair dryer.
[0034] Step 2: Fix the substrate onto the base stage of the magnetron sputtering coating chamber, and evacuate to a background vacuum level of 1×10⁻⁶. -3 Below Pa.
[0035] Step 3: An AlCrYTiZr alloy coating is deposited on the steel substrate by DC magnetron sputtering. The AlCrYTiZr alloy target has an atomic ratio of Al:20%, Cr:20%, Y:20%, Ti:20%, and Zr:20%. The DC power supply is 100-200W, the deposition gas pressure is 0.2Pa, the deposition temperature is room temperature, the substrate rotation speed is 1r / min, the target is directly facing the target and sputtered, and the deposition time is 30min.
[0036] Step 4: The prepared AlCrYTiZr high-entropy alloy coating is cooled to room temperature in the furnace, and the thickness of the resulting AlCrYTiZr high-entropy alloy is 1 μm.
[0037] Step 5: The obtained AlCrYTiZr high-entropy alloy coating is subjected to thermal oxidation in an air atmosphere in a muffle furnace at a temperature of 400℃ for a holding time of 0 min, resulting in the final AlCrYTiZr high-entropy oxide coating. The microstructure and mechanical properties of the prepared AlCrYTiZr high-entropy oxide were characterized. The alloy structure was amorphous, and the elements Al, Cr, Y, Ti, and Zr were uniformly distributed. The hardness was measured to be 15.29 GPa under a 10 mN load by nanoindentation. Electrochemical testing showed a self-corrosion current density of 2.36 × 10⁻⁶. -8 A / cm 2 .
[0038] Example 3 (Sample O-3) Step 1: Polish the substrate to a mirror finish with polishing compound, then ultrasonically clean it in chemically pure acetone and ethanol for 10 minutes in sequence, and then quickly dry it with a hair dryer.
[0039] Step 2: Fix the substrate onto the base stage of the magnetron sputtering coating chamber, and evacuate to a background vacuum level of 1×10⁻⁶. -3 Below Pa.
[0040] Step 3: An AlCrYTiZr alloy coating is deposited on the steel substrate by DC magnetron sputtering. The AlCrYTiZr alloy target has an atomic ratio of Al:20%, Cr:20%, Y:20%, Ti:20%, and Zr:20%. The DC power supply is 100-200W, the deposition gas pressure is 0.2Pa, the deposition temperature is room temperature, the substrate rotation speed is 1r / min, the target is directly facing the target and sputtered, and the deposition time is 30min.
[0041] Step 4: The prepared AlCrYTiZr high-entropy alloy coating is cooled to room temperature in the furnace, and the thickness of the resulting AlCrYTiZr high-entropy alloy is 1 μm.
[0042] Step 5: The obtained AlCrYTiZr high-entropy alloy coating is subjected to thermal oxidation in an air atmosphere in a muffle furnace at a temperature of 400℃ for a holding time of 30 min, resulting in the final AlCrYTiZr high-entropy oxide coating. The microstructure and mechanical properties of the prepared AlCrYTiZr high-entropy oxide were characterized. The alloy structure was amorphous, and the elements Al, Cr, Y, Ti, and Zr were uniformly distributed. The hardness was measured to be 18.25 GPa under a 10 mN load by nanoindentation. Electrochemical testing showed a self-corrosion current density of 2.7 × 10⁻⁶. -9 A / cm 2 .
[0043] Example 4 (Sample O-4) Step 1: Polish the substrate to a mirror finish with polishing compound, then ultrasonically clean it in chemically pure acetone and ethanol for 10 minutes in sequence, and then quickly dry it with a hair dryer.
[0044] Step 2: Fix the substrate onto the base stage of the magnetron sputtering coating chamber, and evacuate to a background vacuum level of 1×10⁻⁶. -3 Below Pa.
[0045] Step 3: An AlCrYTiZr alloy coating is deposited on the steel substrate by DC magnetron sputtering. The AlCrYTiZr alloy target has an atomic ratio of Al:20%, Cr:20%, Y:20%, Ti:20%, and Zr:20%. The DC power supply is 100-200W, the deposition gas pressure is 0.2Pa, the deposition temperature is room temperature, the substrate rotation speed is 1r / min, the target is directly facing the target and sputtered, and the deposition time is 30min.
[0046] Step 4: The prepared AlCrYTiZr high-entropy alloy coating is cooled to room temperature in the furnace, and the thickness of the resulting AlCrYTiZr high-entropy alloy is 1 μm.
[0047] Step 5: The obtained AlCrYTiZr high-entropy alloy coating is subjected to thermal oxidation in an air atmosphere in a muffle furnace at a temperature of 400℃ for a holding time of 60 min, resulting in the final AlCrYTiZr high-entropy oxide coating. The microstructure and mechanical properties of the prepared AlCrYTiZr high-entropy oxide were characterized. The alloy structure was amorphous, and the elements Al, Cr, Y, Ti, and Zr were uniformly distributed. The hardness was measured to be 18.12 GPa under a 10 mN load by nanoindentation. Electrochemical testing showed a self-corrosion current density of 6.1 × 10⁻⁶. -8 A / cm 2 .
[0048] Please see Figure 2To predict the effect of thermal oxidation on the microstructure and phase composition of AlCrYTiZr high-entropy alloys, the enthalpy of mixing of the alloy constituent elements, such as... Figure 2 As shown in the figure, the mixing enthalpy between metal atoms and oxygen atoms is more negative than that between metal atoms. This indicates that metal atoms are more likely to generate new oxide phases different from the matrix phase, meaning that with increasing thermal oxidation holding time, AlCrYTiZr high-entropy oxides may evolve from a single phase to a multiphase phase.
[0049] Please see Figure 3 The O-1 film exhibits a broad diffraction peak at 35°, which gradually shifts to the left and narrows with increasing thermal oxidation time, indicating a transformation from a high-entropy amorphous metal film to a high-entropy amorphous oxide film. The O-2 sample is in a transition state, containing both high-entropy alloy amorphous phase and high-entropy oxide amorphous phase. The thermally oxidized sample shows an iron diffraction peak at 44.7°, corresponding to the iron (110) crystal plane of the substrate, and the peak intensity increases with increasing thermal oxidation time. The high-entropy alloy coating possesses a completely amorphous structure, attributed to the rapid cooling rate of magnetron sputtering and the large difference in atomic size. The "rapid quenching" effect restricts elemental diffusion, preventing grain nucleation and growth. Unheated substrate reduces atomic mobility during deposition. The increased number of high-entropy alloy components and the significant difference in atomic size make the high-entropy alloy system more chaotic, which favors increasing the degree of disordered atomic packing, increasing crystallization resistance, and improving amorphization capability.
[0050] It should be noted that the thermally oxidized samples in this application are mainly amorphous structures for the following reasons: First, compared with metal alloys, the binary oxides in (AlCrYTiZr)O have different crystal structures and lattice parameters. The stable oxide of Zr, ZrO2, has an FCC structure, while the stable oxides of Al and Cr, Al2O3 and Cr2O3, have HCP structures. Y2O3 has a fluorite structure, while TiO2 has a tetragonal rutile structure, which is very unfavorable for the formation of individual oxides. Second, this is also due to the high mixing entropy and large atomic size differences. The high entropy effect enhances the mutual solubility of all elements, inhibits phase separation, and the introduction of small-radius atomic oxygen by thermal oxidation further increases the atomic size differences, leading to severe lattice distortion, which is conducive to the formation of amorphous structures. Finally, the low thermal oxidation temperature prevents the atoms from overcoming the kinetic energy barrier and arranging themselves into an ordered structure.
[0051] Please see Figure 4 , Figure 4 Images (a-d) show SEM images of the surface morphology of AlCrYTiZrO coatings with different O contents. The deposited films and O₂ films have smooth, dense, and continuous surfaces without cracks or peeling. Figure 4As shown in (e~h), the surface particles of the films gradually become finer from O-1 to O-3, but the O-3 and O-4 films exhibit obvious striped structures, with the O-4 film showing a greater number and density of striped structures. This is likely due to volume expansion caused by oxygen dissolution, and the high-entropy alloy film with the longest thermal oxidation time absorbs more oxygen, promoting the formation of the striped structure. The corrosion resistance of the film is closely related to its structure; a loose and porous film is more likely to allow corrosive media to penetrate into its interior, thus promoting film dissolution. This structure increases the contact area between the coating and the corrosive media, which is beneficial to Cl. - The adsorption of these substances results in the longest thermal oxidation time and the worst corrosion resistance.
[0052] Figure 4 (i~l) shows SEM images of the cross-sectional morphology of AlCrYTiZrO coatings with different O contents. All cross-sections are dense, without obvious features or defects such as pinholes or cracks. This is one of the reasons why the samples have good corrosion resistance in 3.5 wt.% NaCl solution; the compact and continuous cross-section provides a good shielding effect, without pores acting as channels for rapid solution diffusion, effectively preventing corrosive media from reaching and eroding the substrate. The O-1 and O-2 samples have a film thickness of approximately 1 μm, with a clear interface between the film and the substrate. The small amount of oxygen solute dissolved in the coating does not change the film thickness. The O-3 sample has a film thickness of 1.18 μm, and the O-4 sample has a film thickness of 1.69 μm. No clear interface was observed between the film and the substrate in either sample. This indicates, on the one hand, that after 30 min of thermal oxidation holding, there is obvious elemental interdiffusion behavior between the film and the substrate, forming a metallurgical bond; on the other hand, it is attributed to furnace cooling, where the coating and the substrate with different coefficients of thermal expansion do not experience thermal stress due to rapid cooling. Cooling the samples in the furnace allows the coating to achieve good bonding or higher adhesion with the substrate. The O-3 sample was approximately 180 nm thicker than the O-1 film, while the O-4 film was 690 nm thicker. Referring to Table 1, the O-4 sample absorbed only about 5 at.% more oxygen than the O-3 sample, yet its thickness increased by about 500 nm. This indicates that the dissolution of oxygen solutes in the O-4 sample coating caused a dramatic volume expansion, resulting in a looser structure. In summary, with prolonged thermal oxidation, the film structure initially gradually densifies before becoming looser.
[0053] according to Figure 4(m~p) Thin film cross-sectional line scan data reveals oxygen diffusion data. In the O-1 film, the oxygen content shows no significant fluctuation from the surface to the substrate, containing only a small amount of oxygen. This may be due to residual water vapor and oxygen-containing gases introduced during the coating synthesis process in the deposition chamber, as well as natural oxidation from the air. In the O-2 film sample, oxygen solutes diffuse uniformly within the film layer. With increasing thermal oxidation time, in the O-3 sample, oxygen solutes show a continuous decreasing trend from the surface to the interior of the film, forming an oxygen solute gradient structure. In the O-4 sample, there is a uniform 1-micron oxide layer from the film surface to the interior, and then the oxygen content gradually decreases along the direction of the substrate interior. The O-4 sample film layer may be completely oxidized. Due to the lack of an oxygen solute gradient structure to act as a transition, the thermal expansion coefficients of the ceramic and X70 steel are severely mismatched, resulting in a loose coating structure and weakened corrosion resistance.
[0054] Samples O-2 and O-3 can be roughly considered as "slices" of the thermal oxidation process of sample O-4. Table 1 shows the elemental content of the membranes. The oxygen content of the samples gradually increased from 13.4 at% in the O-1 film, 31.7 at% in the O-2 film, and 41.4 at% in the O-3 film to 46.0 at% in the O-4 film. With prolonged thermal oxidation, the oxygen content continuously increased. However, the rate of increase slowed down, partly because the oxygen content gradually approached saturation, and partly because a dense oxide layer formed on the film surface, hindering the penetration of oxygen solutes. Thermal oxidation regulated the oxygen content in the film, while simultaneously causing elemental interdiffusion between the substrate and the high-entropy alloy coating, and O-3 formed an oxygen solute gradient structure.
[0055] Table 1. Elemental content of AlCrYTiZrO thin films with different oxygen contents sample O Al Ti Cr Y Zr O-1 13.4 18.6 15.4 17.8 17.6 17.2 O-2 31.7 14.4 11.8 13.7 13.6 14.8 O-3 41.4 12.5 10.1 11.8 11.7 12.5 O-4 46.0 11.5 9.5 11.1 10.5 11.4 Please see Figure 5 To further reveal the microstructure evolution of the coating on the substrate, O-3 coated / X70 steel substrate (6×2.4μm) samples were prepared by FIB for TEM analysis, such as... Figure 5 As shown in (a). Figure 5 As shown in (b), the interface between the coating and the substrate is clear, and the coating thickness is 1.2 µm, confirming that... Figure 4 Analysis of (k). Based on Figure 5 (c) High-resolution image of the coating, showing long-range disordered atomic arrangement and an amorphous structure. Combined with... Figure 5 (d) The SADE pattern proves that the coating has an amorphous structure. Figure 3 The XRD analysis results were consistent. Figure 5(e) Line scan revealed the formation of a high-oxygen-content oxide layer of approximately 200 nm on the film surface. Subsequently, the oxygen solute content decreased towards the substrate, forming an oxygen solute gradient structure. Significant elemental diffusion was observed at the interface between the coating and the X70 steel substrate. Figure 5 (f) The surface scan image at the interface reveals that coating elements diffuse into the substrate, forming a diffusion layer of approximately 60 nm. This is attributed to the slow diffusion effect of the high-entropy alloy, which blocks the diffusion of iron elements from the substrate into the coating. In summary, the O-3 thin film phase structure is an amorphous phase with a dense oxygen-solute gradient structure, forming a natural diffusion barrier layer for corrosive media. Simultaneously, the diffusion layer formed between the film and the substrate enhances the film's adhesion to some extent. The O-3 thin film may exhibit long-term stable and excellent corrosion resistance in a Cl- environment.
[0056] Please see Figure 6 Nanoindentation is used to test the nanomechanical properties of samples, such as... Figure 6 As shown in (a), the load-displacement curves of the prepared films show that the maximum indentation depth of the O-1 film is ~232 nm, and the indentation depth of the thermally oxidized samples at different holding times is approximately equal to ~183 nm, which roughly indicates that the O-1 high-entropy film has better plasticity than the film after thermal oxidation. The O-1 film shows an elastic recovery rate of about 38.7%, indicating that it has good plastic deformation performance. In contrast, the We values of the high-entropy oxide films at different thermal oxidation times are approximately equal, reaching as high as 43.7%, highlighting the strong elastic recovery of the amorphous structure of the high-entropy oxide. This can be attributed to the long-range disordered microstructure of amorphous materials and defects such as dislocations without shear stress transmission
[26] . For the O-1 high-entropy metal coating, H and E are 11.1 GPa and 169.8 GPa, respectively. With the extension of thermal oxidation treatment and holding time, the H and E of the oxide coating gradually increase, while the O-4 film remains almost unchanged, with the highest hardness being 18.28 GPa. Metal oxides are formed during the thermal oxidation of high-entropy alloy films. The ZrO2, Al2O3, Cr2O3, and Y2O3 formed by the metallic elements Zr, Al, Cr, and Y in the thin film are high-hardness ceramic phases. Oxygen dissolution in the film leads to volume expansion, thereby introducing residual compressive stress. Therefore, the surface hardness of HEA treated with thermal oxidation is significantly improved.
[0057] In addition, H / E* and H 3 / E* 2 The H / E* ratio is one of the two important parameters for studying the tribological behavior and wear resistance of protective coatings. The H / E* value represents the material's ability to recover elastic deformation, while H... 3 / E* 2 The value represents the film's resistance to plastic deformation; especially the ratio H. 3 / E* 2The study sensitively provided information on the coating's resistance to plastic deformation and controlled for changes in the coefficient of friction and wear rate. As shown in Table 2, the ratio gradually increased with prolonged thermal oxidation treatment time. This finding indicates that the thermal oxidation treatment of high-entropy metal films transforms the films into high-entropy ceramic films, leading to changes in H / E* and H. 3 / E* 2 The increased ratio likely contributes to a lower coefficient of friction and wear for the coating.
[0058] Table 2. E*, H / E* and H of AlCrYTiZrO coatings with different oxygen contents 3 / E* 2 value sample H(GPa) E*(GPa) H / E* <![CDATA[H 3 / AND* 2 ]]> O-1 11.09 169.819 0.065 0.049 O-2 15.29 213.289 0.071 0.080 O-3 18.28 232.386 0.078 0.117 O-4 18.26 239.315 0.077 0.116 Please see Figure 7 The potentiodynamic polarization curves of AlCrYTiZrO coating films with different O contents are shown below. Figure 7 As shown in (a), it can be seen that the anodic and cathodic branches of the polarization curves of the four samples are asymmetrical. The cathodic branch is much steeper than the anodic branch. From the cathodic branch of the polarization curve, from the O-1 film to the O-3 sample, the cathodic branch shifts to the left sequentially, and at the same potential, the current density gradually decreases by about an order of magnitude. The O-4 sample begins to shift to the right, and the current density increases. According to the anodic polarization branch, except for the O-3 sample, the current density of the other samples increases rapidly with the increase of polarization potential. The Ecorr values of all four groups of samples are low enough, indicating that the oxide protective layer is easy to form on the film surface. Among them, the O-1 and O-3 samples both show a passivation region at the corrected potential, and the current density in this region changes slowly with the change of potential.
[0059] The low current density of the O-3 film originates from the dense amorphous structure of oxygen solute formed by thermal oxidation. The self-corrosion potential of the thermally oxidized coating shifts negatively compared to the O-1 film, indicating that thermal oxidation may exacerbate corrosion. Table 3 summarizes the corrosion potential (Ecorr) and corrosion current density (Icorr) of AlCrYTiZrO HEA with different oxygen contents in 3.5 wt.% NaCl solution. The self-corrosion current density first decreases and then increases, consistent with the earlier assertion that the coating first densifies and then loosens in structure. The dense amorphous structure can limit the erosion of the substrate by the corrosive medium, enhancing corrosion resistance. The O-3 coating at 10 -9 A / cm 2 The Icorr value at the same level is one order of magnitude lower than that of the O-1 coating, indicating that the O-3 coating is not easily corroded in the current corrosive environment.
[0060] Table 3. Electrochemical test results of AlCrYTiZrO films with different oxygen contents in 3.5 wt.% NaCl solution sample <![CDATA[E corr (V)]]> <![CDATA[I corr (A / cm 2 )]]> O-1 -0.379 <![CDATA[3.93×10 -8 ]]> O-2 -0.465 <![CDATA[2.36×10 -8 ]]> O-3 -0.519 <![CDATA[2.7×10 -9 ]]> O-4 -0.489 <![CDATA[6.10×10 -8 ]]> Figure 7 (b) and (c) show the Nyquist and Bode plots of the electrochemical impedance spectroscopy (EIS) of high-entropy alloy samples with different oxygen contents after immersion in 3.5 wt.% NaCl solution for half an hour. Figure 7 As shown in (b), all samples exhibited typical capacitive responses represented by slanted lines or truncated semicircles, indicating the presence of an oxide layer at the interface that restricts the reaction between the X70 steel substrate and the electrolyte. The significant difference in semicircle radii suggests variations in the corrosion resistance of high-entropy films with different microstructures. Compared to high-entropy alloy coatings, the capacitance ring size of the thermally oxidized samples first increased significantly and then decreased with increasing holding time. Specifically, the capacitance ring size of the O-3 sample increased significantly, indicating an increase in the charge transfer resistance of the coating and better capacitive behavior of the passivation film. The protective performance of the thermally oxidized coating was significantly improved.
[0061] exist Figure 7 (c) The Bode plot shows solution resistance and charge transfer resistance at both high and low frequencies. In the 101 Hz–104 Hz range, the impedance modulus relationship is: O-4 > O-3 > O-1 > O-2 films. At low frequencies (<101 Hz), the impedance modulus of O-4 begins to decrease. The impedance modulus value at 0.1 Hz is used as an evaluation value for the charge-binding ability of the passivation film. The impedance modulus first increases and then decreases with increasing oxygen content. The O-3 film has the highest impedance modulus value, indicating that its film has the strongest charge-blocking ability in 3.5% NaCl solution. The oxygen-solute amorphous structure film generated by thermal oxidation for 30 min exhibits better stability and corrosion resistance. Except for O-4, the phase angle peaks of the other samples are at -80°, and the peak spread is very broad, indicating high capacitance or corrosion inhibition capabilities.
[0062] To directly understand the physicochemical behavior of the substrate / film / solution system, EIS data were simulated using a typical equivalent circuit (EEC). Figure 7 (d) shows the equivalent circuit, and the fitting parameters are listed in Table 4. The equivalent circuit includes Rs and Rct, which represent the solution resistance and charge transfer resistance between the working electrode and the reference electrode, respectively. It is noteworthy that all chi-square (χ²) values... 2 The value remains at 10. -3 This indicates that the error is within an acceptable range. Considering the dispersion effect caused by the non-uniformity, porosity, and roughness of the sample surface film, the capacitance is usually a non-ideal capacitance. Therefore, CPE is used instead of pure capacitive elements in the EEC model.
[0063] Table 4. EIS fitting results of different samples in 3.5 wt.% NaCl based on the equivalent circuit model. sample <![CDATA[R ct (Ω•cm 2 )]]> <![CDATA[R sol (Ω•cm 2 )]]> <![CDATA[Y0(Ω − 1 •cm − 2 •sn)]]> n <![CDATA[χ 2 ]]> O-1 <![CDATA[3.16×10 5 ]]> 30.01 <![CDATA[4.63×10 -6 ]]> 0.89 <![CDATA[6.65×10 -4 ]]> O-2 <![CDATA[8.66×10 5 ]]> 31.03 <![CDATA[5.26×10 -6 ]]> 0.94 <![CDATA[4.42×10 -4 ]]> O-3 <![CDATA[5.56×10 6 ]]> 29.98 <![CDATA[2.76×10 -6 ]]> 0.9 <![CDATA[2.83×10 -3 ]]> O-4 <![CDATA[2.55×10 5 ]]> 61.93 <![CDATA[2.30×10 -6 ]]> 0.86 <![CDATA[8.22×10 -3 ]]> According to Table 4, the R values for all coatings sValue at 30Ω·cm 2 and 60Ω·cm 2 Between. Compared with high-entropy alloy films, the thermally oxidized sample improved R. ct Value. The highest R value obtained from the sample after 30 min of thermal oxidation. ct It is 5.56 × 10 6 Ω•cm 2 The results of potentiodynamic polarization and electrochemical impedance spectroscopy tests were basically consistent. The oxygen-solute amorphous structure film constructed by thermal oxidation significantly improved the corrosion resistance of X70 steel substrate in 3.5 wt.% NaCl solution.
[0064] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention. The scope of protection claimed by the appended claims and their equivalents is defined.
Claims
1. A method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating, characterized in that, Includes the following steps: Step S11: The substrate after ultrasonic cleaning and drying is sent into the cavity, and a high-entropy alloy coating is deposited on the surface of the substrate by magnetron sputtering. Then, it is cooled to room temperature. The high-entropy alloy target is an AlCrYTiZr alloy target with an equiatomic ratio. Step S12: The substrate containing the high-entropy alloy coating is placed in an oxidation furnace, thermally oxidized in an air atmosphere, and then cooled to room temperature with the furnace to obtain the AlCrYTiZrO high-entropy oxide coating.
2. The method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating according to claim 1, characterized in that, The AlCrYTiZrO high-entropy oxide coating is an amorphous structure containing an oxygen solute gradient, and the oxygen solute gradually decreases from the coating surface toward the substrate. AlCrYTiZr alloying elements and matrix elements diffuse into each other at the interface between the coating and the matrix, forming a diffusion layer.
3. The method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating according to claim 2, characterized in that, The AlCrYTiZrO high-entropy oxide coating has a thickness of 1~2 μm, and the diffusion layer has a thickness of 50~70 nm.
4. The method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating according to claim 1, characterized in that, The hardness of the AlCrYTiZrO high-entropy oxide coating is 15.29~18.28 GPa, and the self-corrosion current density is 2.36×10⁻⁶. -8 ~2.7×10 -9 A / cm 2 .
5. The method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating according to claim 1, characterized in that, In step S11, the magnetron sputtering uses a DC power supply of 100-200W, a deposition gas pressure of 0.2-0.3Pa, a deposition time of 30min, and a deposition temperature of room temperature.
6. The method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating according to claim 1, characterized in that, In step S12, the temperature of thermal oxidation is below 450℃, the heating rate is 15~20℃ / min, and the holding time is 0~60min.
7. The method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating according to any one of claims 1 to 6, characterized in that, In step S11, before magnetron sputtering, the substrate is subjected to plasma bombardment cleaning, and then the high-entropy alloy target is pre-sputtered.
8. The method for preparing an oxygen-solute gradient amorphous high-entropy alloy oxide coating according to any one of claims 1 to 6, characterized in that, The atomic ratio of each element in the high-entropy alloy target is 20%.
